2003
DOI: 10.1055/s-2003-37950
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Sonographic Diagnosis of Klippel-Trenaunay-Weber Syndrome Associated with Umbilical Cord Hemangioma

Abstract: Klippel-Trenaunay-Weber syndrome (KTW), also known as angio-osteohypertrophy syndrome, is a complex developmental disorder characterized by asymmetric hemi-hypertrophy of limbs and trunk due to bony and soft tissue overgrowth that may extend across the midline, varicose veins, and cutaneous hemangiomata. This rare syndrome has been previously described in the prenatal period by ultrasonography, and in literature, there are quite different presentation of cases. We describe a case suggested as a KTW syndrome by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Interestingly, two reports of prenatal ultrasonographic diagnosis of umbilical cord hemangioma in association with Klippel-Trenaunay-Weber syndrome have been reported. 258,259 Sahinoglu et al reported a spheric weakly echogenic mass within the umbilical cord, later confirmed at postpartum examination as an umbilical cord hemangioma. 258 Recently, in 2020, Yu et al reported prenatal sonographic diagnosis of Klippel-Trenaunay-Weber syndrome (mainly manifesting hypertrophy of the left thigh) associated with an umbilical cord hemangioma.…”
Section: Umbilical Cord Hemangioma In Association With Klippel-trenaunay-weber Syndromementioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, two reports of prenatal ultrasonographic diagnosis of umbilical cord hemangioma in association with Klippel-Trenaunay-Weber syndrome have been reported. 258,259 Sahinoglu et al reported a spheric weakly echogenic mass within the umbilical cord, later confirmed at postpartum examination as an umbilical cord hemangioma. 258 Recently, in 2020, Yu et al reported prenatal sonographic diagnosis of Klippel-Trenaunay-Weber syndrome (mainly manifesting hypertrophy of the left thigh) associated with an umbilical cord hemangioma.…”
Section: Umbilical Cord Hemangioma In Association With Klippel-trenaunay-weber Syndromementioning
confidence: 98%
“…Interestingly, two reports of prenatal ultrasonographic diagnosis of umbilical cord hemangioma in association with Klippel-Trenaunay-Weber syndrome have been reported. 258 , 259 …”
Section: Umbilical Cord Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, a hemangioma was located in the umbilical cord. Sahinoglu 14 has also reported a case of KTWS associated with umbilical cord hemangioma. Our case is the second reported case of KTWS with a complication of umbilical cord hemangioma.…”
Section: Discussionmentioning
confidence: 95%
“…A deep tissue cavernous hemangioma may gradually appear and aggravate in later childhood. The prenatal ultrasound features in utero have been described in many studies[ 8 , 12 - 14 ]. They include marked asymmetrical hypertrophy of limbs, thickening of the subcutaneous soft tissue, multiple cystic lesions, increasing blood flow signals, dilated veins or persistence of embryonic veins.…”
Section: Discussionmentioning
confidence: 99%